Universal health coverage from multiple perspectives: a synthesis of conceptual literature and global debates - Abiiro, Gilbert Abotisem; De Allegri, Manuela (BMC international health and human rights, 2015)
There is an emerging global consensus on the importance of universal health coverage (UHC), but no unanimity on the conceptual definition and scope of UHC, whether UHC is achievable or not, how to move towards it, common indicators for measuring its progress, and its long-term sustainability. This has resulted in various interpretations of the concept, emanating from different disciplinary perspectives. This paper discusses the various dimensions of UHC emerging from these interpretations and argues for the need to pay attention to the complex interactions across the various components of a health system in the pursuit of UHC as a legal human rights issue.